Sticky Prices and Inflation Expectations in Norway - Solveig K. Erlandsen (Norges Bank, 2014)
Some consumer prices are changed often, while others are changed infrequently. In this memo, I investigate whether Norwegian consumer prices that are changed often - called flexible prices in this memo - and prices that are changed relatively infrequently - sticky prices - have different information content. I find some indications that sticky prices contain more information about inflation expectations in the medium term than flexible prices. This is as expected and in line with findings in other countries.
hdl:11250/2506900
Keywords: 330